2007
DOI: 10.1073/pnas.0706209104
|View full text |Cite
|
Sign up to set email alerts
|

Phycobilin:cystein-84 biliprotein lyase, a near-universal lyase for cysteine-84-binding sites in cyanobacterial phycobiliproteins

Abstract: Phycobilisomes, the light-harvesting complexes of cyanobacteria and red algae, contain two to four types of chromophores that are attached covalently to seven or more members of a family of homologous proteins, each carrying one to four binding sites. Chromophore binding to apoproteins is catalyzed by lyases, of which only few have been characterized in detail. The situation is complicated by nonenzymatic background binding to some apoproteins. Using a modular multiplasmidic expression-reconstitution assay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
137
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 106 publications
(152 citation statements)
references
References 74 publications
6
137
2
3
Order By: Relevance
“…This elution order could be estimated from the calculated mass of the tryptic peptides, with a-Cys-81 at 2,337.6 Da and b-Cys-81 at 852.0 Da. This was consistent with results from Zhao et al (2007). The identical retention time of the rAPC and native APC digestions suggested that the binding site of PCB in rAPC was identical to the native protein.…”
Section: Rapc Identification and Characteristicssupporting
confidence: 89%
See 2 more Smart Citations
“…This elution order could be estimated from the calculated mass of the tryptic peptides, with a-Cys-81 at 2,337.6 Da and b-Cys-81 at 852.0 Da. This was consistent with results from Zhao et al (2007). The identical retention time of the rAPC and native APC digestions suggested that the binding site of PCB in rAPC was identical to the native protein.…”
Section: Rapc Identification and Characteristicssupporting
confidence: 89%
“…PCC 7002 and Anabaena sp. PCC 7120 (Saunee et al 2008;Shen et al 2008;Zhao et al 2007). Phylogenetic analyses of cyanobacteria based on their PCB lyases suggested that the heterodimeric lyases CpcS-1 and CpcU are also responsible for PCB attachment in Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of chromophorylated phycobiliprotein was detected by the emission at 645 nm for PCB-containing chromoproteins (15), and at 575 nm for PEB-containing chromoproteins (13). Complete spectra in the 350 to 700 nm range were recorded to verify correct attachment and the absence of spontaneous addition products (6).…”
mentioning
confidence: 99%
“…Lyase Activity Assay-Chromophore reconstitution with apo-phycobiliprotein was assayed as described before (13,15,25) using the following standard reaction conditions: KPB (500 mM, pH 7.5) containing NaCl (150 -200 mM), CpcS1 (or mutants, 10 -30 M), and apo-phycobiliprotein (5-30 M). PCB (final concentration ϭ 2-15 M) was added as a concentrated DMSO solution where the final concentration of DMSO in the reaction mixture was 1% (v/v).…”
mentioning
confidence: 99%